2001
DOI: 10.1097/00001648-200107000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Residential Radon and Lung Cancer among Never-Smokers in Sweden

Abstract: In this study, we attempted to reduce existing uncertainty about the relative risk of lung cancer from residential radon exposure among never-smokers. Comprehensive measurements of domestic radon were performed for 258 never-smoking lung cancer cases and 487 never-smoking controls from five Swedish case-control studies. With additional never-smokers from a previous case-control study of lung cancer and residential radon exposure in Sweden, a total of 436 never-smoking lung cancer cases diagnosed in Sweden betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(51 citation statements)
references
References 28 publications
3
48
0
Order By: Relevance
“…Lagarde et al (2001) conducted a casecontrol study of lung cancer among nonsmokers in Sweden to examine the effect of residential radon exposure and found an ERR coefficient that was similar to the overall risk estimate obtained from the metaanalyses of domestic radon studies. Recently, Wang et al (2002b) have reported the results of a case-control study of lung cancer incidence during January 1994 to April 1998 in a high residential radon area of Gansu Province in China.…”
Section: Introductionmentioning
confidence: 65%
“…Lagarde et al (2001) conducted a casecontrol study of lung cancer among nonsmokers in Sweden to examine the effect of residential radon exposure and found an ERR coefficient that was similar to the overall risk estimate obtained from the metaanalyses of domestic radon studies. Recently, Wang et al (2002b) have reported the results of a case-control study of lung cancer incidence during January 1994 to April 1998 in a high residential radon area of Gansu Province in China.…”
Section: Introductionmentioning
confidence: 65%
“…Among them, most were excluded after abstract because they were occupational studies on miners, no case control studies, no relevant exposure or endpoint, and reviews. After assessing the full-text of the 38 relevant articles, we identified 22 eligible studies for meta-analysis (Blot et al, 1990;Schoenberg et al, 1990;Pershagen et al,1992Pershagen et al, , 1994Alavanja et al, 1994Alavanja et al, , 1999Létourneau et al, 1994;Auvinen et al, 1996;Ruosteenoja et al, 1996;Darby et al, 1998;Field et al, 2000;Sobue et al, 2000;Lagarde et al, 2001;Pisa et al, 2001;Barros-Dios et al, 2002;Wang et al, 2002;Baysson et al, 2004;Bochicchio et al, 2005;Wichmann et al, 2005;Sandler et al, 2006;Thompson et al, 2008;Wilcox et al, 2008). Seven studies were excluded for previous mete-analysis (Lubin and Boice, 1997;Pavia et al, 2003) and combined analysis in Europe, North America or China Darby et al, 2005;Krewski et al, 2005;Wang et al, 2005;Darby et al, 2006).…”
Section: Literature Searchmentioning
confidence: 99%
“…3 Cigarette smoking is attributable to approximately 85-90% of all lung cancer, and certain environmental and occupational exposures, such as asbestos and radon, have also been linked to lung cancer development. 4,5 The incidence of lung cancer is rising in women and declining in men as a result of changed smoking behavior. 6 The changing histological patterns in lung cancer probably relate to changes in the composition of cigarettes.…”
mentioning
confidence: 99%